Trust in Tourism Governance Partnership in Managing Sustainable Marine Tourism in Southwest Papua Province - Lamatenggo, Yusdi Nurdin; Ibrahim, Muh. Akmal; Musa'ad, Muhammad (KnE Social Sciences, 2025)
Marine tourism is an activity that relies on the appeal of natural panoramas and coastal marine environments with special interest activities in the form of fishing, snorkeling, swimming, recreation, and others, which utilize coastal areas as their main vehicle. This study aims to analyze tourism governance partnerships in the management of sustainable marine tourism in Southwest Papua Province. The trust element relates to building trust between actors involved in the development of sustainable marine tourism. This study uses qualitative analysis, using data collection methods through in-depth interviews and documentation studies to explore trust between multiple actors in building and maintaining relationships in sustainable marine tourism management in Southwest Papua Province. Data sources consist of primary and secondary data, while data analysis is carried out using interactive methods. Informants in this study are actors involved in sustainable marine tourism management in Southwest Papua Province. The results of the study indicate that trust in tourism governance partnership in the management of sustainable marine tourism in the West Papua Province is improving the quality and quantity of actors formulating shared vision and targets. Communication was built through a tourism coordination forum. In maintaining trust between actors, consistency in action, transparency, and respecting the role and rights of each actor. Maintaining commitment in the management of marine tourism, the tourism office and the indigenous community to make an agreement or memorandum of understanding (MoU). However, building trust there are still obstacles, namely that coordination between actors is not yet fully optimal in building joint marine tourism branding and other obstacles.